Ropeginterferon alfa-2b treatment in a young patient with multi-refractory polycythemia vera and double JAK2 gene mutation: a case report - Ligia, Silvio; Scalzulli, Emilia; Carmosino, Ida; Palumbo, Giovanna; Molinari, Maria Chiara; Poggiali, Rebecca; Costa, Alessandro; Bisegna, Maria Laura; Martelli, Maurizio; Breccia, Massimo (Frontiers in Oncology, 2024)
This case report presents a 3-year-old female patient initially diagnosed with polycythemia vera (PV) in 2001. The patient exhibited elevated red blood cell (RBC) counts, high hemoglobin (Hb) levels, hyperleukocytosis, and moderate thrombocytosis, with sporadic abdominal pain and significant splenomegaly. Despite various treatments, including phlebotomies, hydroxyurea, and alphainterferon, the patient struggled to maintain optimal hematocrit levels and experienced persistent symptoms. Subsequent genomic analysis revealed a rare JAK2 G301R mutation alongside the canonical JAK2 V617F mutation, potentially contributing to disease severity. In 2023, the patient started Ropeginterferon alfa-2b, leading to improved hematological parameters and symptom relief. The case underscores the challenges in managing PV, particularly in young patients, and highlights the potential clinical significance of additional JAK2 mutations/variants and the potential benefits of Ropeginterferon alfa-2b in achieving better disease control.